ANAEROBIC BIODIGESTION OF MUSACEAE RESIDUES: ECUADOR CASE - Solano-Apuntes, Alex (2022)
Ecuador is a country where three sectors with bioenergy potential have been identifi ed: fi rstly, agriculture, with products such as rice, bananas, cocoa, coff ee, sugar cane, hard corn, African palm, hearts of palm, pineapple, and plantain. Th e second is the livestock sector, with poultry, pig, and beef activities. Th e third is the forester. The residues generated by Musaceae (Banana and Plantain) are not well used effi ciently because they are disposed of in the open air and present environmental and economic problems for banana growers, however, this fruit off ers the opportunity to obtain valueadded bioproducts due to its chemical composition. Musaceae crops have been established predominantly in lands with a high mechanized agricultural vocation and with great hydrological wealth, these areas are of medium and high vulnerability to productive processes, and are not recommended for intensive urban, industrial, mining, and recreational development. Th e correct management of organic waste is achieved through diff erent treatments that involve recycling these organic materials, transforming them into value-added products. The recycling of organic matter has received a strong boost with the high cost of chemical fertilizers, with the search for non-traditional energy alternatives, as well as the need for decontamination and waste disposal routes. Aerobic digestion is a process carried out by various groups of microorganisms, mainly bacteria, and protozoa, which, in the presence of oxygen, act on dissolved organic matter, transforming it into harmless end products and cellular matter. Th e present investigation arises as an alternative for the management and use of the residual biomass of the Musaceae, mainly in the organic waste that they generate, and thus give it an adequate use through the production of biogas in Ecuador.